Elimination of hop latent viroid upon developmental activation of pollen nucleases - Matousek, Jaroslav; Orctová, Lidmila; Skopek, Josef; Pesina, Karel; Steger, Gerhard (Biological chemistry, 2008)
Hop latent viroid (HLVd) is not transmissible through hop generative tissues and seeds. Here we describe the process of HLVd elimination during development of hop pollen. HLVd propagates in uninucleate hop pollen, but is eliminated at stages following first pollen mitosis during pollen vacuolization and maturation. Only traces of HLVd were detected by RT-PCR in mature pollen after anthesis and no viroid was detectable in in vitro germinating pollen, suggesting complete degradation of circular and linear HLVd forms. The majority of the degraded HLVd RNA in immature pollen included discrete products in the range of 230-100 nucleotides and therefore did not correspond to siRNAs. HLVd eradication from pollen correlated with developmental expression of a pollen nuclease and specific RNAses. Activity of the pollen nuclease HBN1 was maximal during the vacuolization step and decreased in mature pollen. Total RNAse activity increased continuously up to the final steps of pollen maturation. HBN1 mRNA, which is abundant at the uninucleate microspore stage, encodes a protein of 300 amino acids (34.1 kDa, isoeletric point 5.1). Sequence comparisons revealed that HBN1 is a homolog of S1-like bifunctional plant endonucleases. The developmentally activated HBN1 and pollen ribonucleases could participate in the mechanism of HLVd recognition and degradation.
Keywords: sekvence nukleotidů; ribonukleasy; Substrate Specificity; latence viru; Molecular Sequence Data; molekulární sekvence - údaje; viroidy; Humulus; Ribonucleases; Enzyme Activation; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; Amino Acid Sequence; Germination; Virus Latency; Base Sequence; Pollen; substrátová specifita; Viroids; pyl; aktivace enzymů; klíčení; sekvence aminokyselin